QUANTIFICATION OF STREPTOCOCCUS SANGUINIS ISOLATED FROM DENTAL PLAQUE AND SALIVA OF SUBJECTS WITH AND WITHOUT CORONARY HEART DISEASE “ ANALYSIS USING REAL-TIME PCR: KUANTIFIKASI STREPTOCOCCUS SANGUINIS YANG DIISOLASI DARI PLAK DAN SALIVA GIGI SUBYEK DENGAN DAN TANPA PENYAKIT JANTUNG KORONER DENGAN MENGGUNAKAN PCR REAL-TIME - Nasution, Aini Hariyani; Kemal, Yulianti; Lessang, Robert; Bachtiar, Boy (Dentika: Dental Journal, 2017)
Coronary Heart Disease (CHD) is the major cause of death in most countries in the world. Gram-positive and Gram-negative bacteria have been identified in bacteremia cases and known to have a role in various vascular diseases, including Streptococcus sanguinis which is most frequently isolated from endocarditis patients and often associated with CHD. The purpose of this study was to analyze the number of Streptococcus sanguinis isolated from dental plaque and saliva of subjects with and without CHD. Bacterial colonies isolated from the dental plaque and saliva of 16 subjects without CHD and 8 subjects with CHD were planted in Mitis salivarius agar, and then the DNA was extracted and quantified with a Real-Time PCR technique using 16S rRNA specific primers. The quantification of Real-Time PCR showed that there was a difference in the number of S. sanguinis between the two groups of subjects, but an unpaired T-test showed that the difference was not statistically significant. Furthermore, the number of S. sanguinis from dental plaque in CHD subjects tends to be higher than that of non-CHD subjects whereas the number of S. sanguinis from saliva in non-CHD subjects tends to be higher than that of CHD subjects.